MERANCANG MANAJEMEN SUMBER DAYA INSANI IBU RUMAH TANGGA, REMAJA DAN ANAK-ANAK DI DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Azizah Mursyidah; Sella Oktavani (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This community service explores the extent of the human resources of housewives, youth and children in Central Cibitung Village, Tenjolaya District, Bogor Regency. Within the scope of community service, human resource management (MSDI) is designed to increase the effectiveness of human resources in society. The goal is to provide learning to the public about effective MSDI. To achieve these goals includes planning, organizing, implementing, and controlling. With the activities carried out on and by housewives, teenagers and children. outreach and training. It is expected to develop creativity, and the quality of society. In this community service, the community plays an active role in activities to advance the community.